Ethnicity, Politics and Economic Performance. - Collier, P (Blackwell Publishing, 2000)
The paper investigates the effects of ethnic diversity on economic performance. Previous studies have found that diversity has various detrimental microeconomic effects, tending to reduce public sector performance, and has large detrimental effects on the overall growth rate. I develop a simple model of the effect of ethnic diversity on a government decision problem in which there is a tradeoff between growth and distribution, in the contexts of democracy and dictatorship. I find that in democracy ethnic diversity has no effect upon the decision, whereas in dictatorship ethnic diversity leads to a government choice that reduces the growth rate. I then test these propositions on two data sets. The first is for 94 countries over the period 1960-90. I find that whether diversity adversely affects overall economic growth depends upon the political environment. Diversity is highly damaging to growth in the context of limited political rights, but is not damaging in democracies. The second is for World Bank projects in 89 countries. I find that the same relationship between diversity and democracy affects the proportion of projects that are successful.